Can the New Neutrino Telescopes Reveal the Gravitational Properties of Antimatter? - Dragan Slavkov Hajdukovic (Advances in Astronomy)
We argue that the hypothesis of the gravitational repulsion between matter and antimatter can be tested at the Ice Cube, a neutrino telescope, recently constructed at the South Pole. If there is such a gravitational repulsion, the gravitational field, deep inside the horizon of a black hole, might create neutrino-antineutrino pairs from the quantum vacuum. While neutrinos must stay confined inside the horizon, the antineutrinos should be violently ejected. Hence, a black hole (made from matter) should behave as a point-like source of antineutrinos. Our simplified calculations suggest that the antineutrinos emitted by supermassive black holes in the centre of the Milky Way and Andromeda Galaxy could be detected by the new generation of neutrino telescopes.